Communicating with Key Publics in Crisis Communication: The Synthetic Approach to the Public Segmentation in CAPS (Communicative Action in Problem Solving). (22nd December 2015) - Kim, Young; Miller, Andrea; Chon, Myoung‐Gi
Abstract : The purpose of this study is to identify and understand key publics and their communication behaviours in crisis communication, using the public segmentation framework which has been rarely used in crisis communication. In doing so, the study quantitatively tests a new theoretical framework of Communicative Action in Problem Solving, classifying eight types of aware and active publics. Through the new framework of public segmentation, the survey results from 1, 113 participants substantiate eight types of active and aware publics, as well as their communicative characteristics in a crisis situation. The study finds that the aware and active publics are, as the key publics, more likely to have negative behavioural intentions toward an organization. Theoretical and practical implications are discussed.